A city to sell : digitalization and financialization of the housing market in Cape Town : stratification & segregation in the emerging global city - (:unkn) unknown (My University, 2020)
This thesis investigates the digitalization and financialization of the housing market in Cape Town, South Africa. Borrowing from economic sociology and urban geography, I develop the concept of "housing market assemblage" to both analyze and conceptualize how the evolution of market structures renews contemporary patterns of social stratification and urban segregation in an emerging global city. To do so, I use mixed methods that combine qualitative and quantitative approaches. Over 18 months of fieldwork, I conducted interviews with market professionals (real estate agents, property developers, mortgage brokers, bankers, investors) and households, while engaged in participant observation of a local estate agency in Cape Town's largest black township (Khayelitsha). Furthermore, I built a database of 900,000 residential real estate transactions and employed multivariate statistics and spatial analysis to track the evolution of prices and mortgages across the post-apartheid urban space. The thesis demonstrates how the housing market was reconfigured as a continuous flow of data through the adoption of digital platforms and the progressive making of housing as a financial asset on both the buyer's and rental markets. The market creates two filtering mechanisms with deep stratifying effects : (i) housing affordability is determined by the unequal spatial distribution of housing prices, on the one hand, and the social and racialized distribution of income and family assets, on the other, in a context of highly selective lending practises (ii) the hegemonic use of credit scoring technologies that allow the automated classification of South African citizens through an information dragnet of unprecedented sophistication and depth, both for the Global North and the Global South. Banks and newly formed corporate landlords use credit scoring to classify & select mortgage recipients and tenants, in a context of household indebtedness and enduring racial i
Keywords: African Research